A systematic review of interventions for creativity enhancement - Arriaga, P.; Paiva, A.; Paiva, A.; Paiva, A.; Paiva, A.; Guy Hoffman (XV Phd Meeting in Psychology, 2019)
Creativity plays a central role in children's education, development and well-being, being considered a crucial skill to thrive in life. Given its importance, researchers and educators have been highlighting the need to enhance creativity across the life-span. However, a decline in creative skills around elementary school age is documented. Therefore, there is a need understand how particular programs and interventions promote creativity at this early age. The goal of this systematic review was two-fold: firstly, collect and summarize research findings on interventions and training programs that have been proposed to foster creativity in children of between 5-12 years old. We used the PRISMA-P guidelines to systematically review 3.613 articles published from 1950-2018 and have identified 48 articles of interest. In this talk, we will present a summary of evidence about interventions for creativity dedicated to children present in these 48 included articles, which has not yet been done. A quality assessment for each of the included articles was conducted according to the STROBE guidelines. Secondly, we clarified trending terms used in creativity research that otherwise remain sparse and under different literary definitions, by creating a coding scheme that includes key-concepts on creativity research. This resulted in a nomenclature clarification to ground further discussions surrounding creativity, within and outside the field. The developed coding scheme was also used to analyze the existing programs and interventions dedicated to creativity. We related our findings with policymakers for creativity research, highlighting the best practices for creativity stimulation in children.